Analisis Penerapan Standar Akuntansi, Tingkat Kesadaran dan Kesiapan Pelaku Umkm Dalam Menyusun Laporan Keuangan - Siahaaan, Mariati (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important thing for the economy. It has also developed rather quickly, making it one of the sectors influencing the Indonesian economy. For creating financial reports, Indonesia now uses specialised Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This study aims to determine whether MSMEs in Batam City's Sungai Beduk District have adopted accounting standards in their financial reports, whether MSME actors are aware of the need to prepare financial reports in accordance with SAK EMKM, and whether MSME actors are prepared to do so. The method used is descriptive qualitative. Both primary and secondary sources of data were used. While secondary data came from Batam City's Department of Cooperatives and Micro Enterprises, primary data came straight from surveys, in-depth interviews, and observations. According to the study's findings, MSMEs in Batam City's Sungai Beduk District have not adopted Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM for prepare financial reports), MSMEs are aware of prepared financial report, and MSMEs are not yet readiness to create financial reports. From three sample used there are two MSMEs who have prepared financial reports but not following to accounting standards, and the other one have not prepared financial reports.